An Analysis of Health Benefits of Carrot (International Journal of Innovative Research in Engineering & Management, 2023)
carrot (Daucus carota subsp. sativus) is  root vegetation that available in diversity of colors,  comprising purple, black, red, white, & yellow. Carrots  include carotenids, flavonoid, polyacetylens, vitamins, & minerals, all which provide diversity of nutritional health advantages. Carotenoids, polyphenols, & vitamins  found in carrots function as antioxidants, anticarcinogens,  & immune enhancers, proving ancient saying that carrots  are excellent for eyes. Carrot has shown to have anti diabetic, cholesterol & cardiac disease reducing, anti hypertensive, hepatoprotective,renoprotective,&woundhealingproperties. Carrotseedextractshavecardio-hepatoprotective,antibacteral, antifungal, anti inflammatory, & analgesic properties. All of se topics are  covered in this review essay. Carrots are important tuber  crop that is high in biochemical elements like carotenoid  and soluble fiber, as well as variety of other functional  elements with wellness properties.. Carrot consumption is  gradually rising as a result of its recognized as a valuable  source of natural antioxidants with anticancer properties.  Apart from being utilized in salads & curries in India,  carrot roots may be professionally processed into  nutritionally rich processed goods like as juice,  concentrate, dry powder, tinned, preserve, c&y, pickle, & gazrailla. Carrot pomace, which contains approximately  50% -carotene, may be used to enhance goods such as  cake, bread, & biscuits, as well as to make a diversity of  useful products. nutritional content, health-promoting  phytonutrients, functional characteristics, product  creation, & by-products usage of carrot & carrot pomace,  as well as ir prospective application, are all highlighted in  this study.
Keywords: Carrot; Health; Pigment; Plant; Vegetable